What’s Left? La izquierda como “optimismo social” (Devenires, 2025)
The left is in crisis. But the way we think about the left is also in crisis. The first objective of this article is to determine the origin of left-wing thought; it is assumed to reside in Enlightenment thought and, as Judith N. Shklar stated, in its “social optimism.” Another issue to be addressed is that of temporal orientation: although left-wing thought is still understood as projecting itself into the future, the question of its relation to the past must be raised today. This article will argue in favor of becoming aware of the achievements of left-wing movements, in whose defense left-wing thought and politics should be committed, because it is precisely these achievements that have been destroyed in the course of forty years of neoliberal offensive as well as in the current phase of authoritarian populism. Finally, we will ask what we are to make of current “left-wing” movements, which can be subsumed under terms such as “cultural left,” “lifestyle left,” “woke left,” or simply “aesthetic left”. We will also ask whether a left that goes back to Marx is necessarily an alternative to those. The underlying question is: What’s left?
Keywords: Critical Humanism; Enlightenment; Marx; Judith N. Shklar